A visible light-controllable Rho kinase inhibitor based on a photochromic phenylazothiazole. Issue 93 (9th November 2021) - Matsuo, Kazuya; Thayyil, Sampreeth; Kawaguchi, Mitsuyasu; Nakagawa, Hidehiko; Tamaoki, Nobuyuki
Abstract : Rho-associated coiled-coil-containing protein kinase (ROCK) is a serine–threonine kinase whose inhibitors are useful for the regulation of the actomyosin system. Abstract : Rho-associated coiled-coil-containing protein kinase (ROCK) is a serine–threonine kinase whose inhibitors are useful for the regulation of the actomyosin system. Here, we developed a photoswitchable ROCK inhibitor based on a phenylazothiazole scaffold. The reversible trans – cis isomerization by visible light stimuli enabled us to manipulate ROCK activities in vitro and in cells.